A Qualitative Study on the Doctrine of Privity to Circumvent its Effect on Subcontractor’s Payment Claim - See Zhi Yan; Mohd Suhaimi Mohd-Danuri; Othman Mohamed; Fadzida Ismail; Noorfajri Ismail (Malaysian Institute of Planners, 2024)
Volume: 21 Issue: 5(2023),Page17–31